2019
DOI: 10.2459/jcm.0000000000000735
|View full text |Cite
|
Sign up to set email alerts
|

Nonvalvular atrial fibrillation in high-hemorrhagic-risk patients: state of the art of percutaneous left atrial appendage occlusion

Abstract: Atrial fibrillation is the most common cardiac arrhythmia and its prevalence is constantly increasing. The main complications related to atrial fibrillation are death and major stroke. Oral anticoagulant therapy is the cornerstone of management of atrial fibrillation patients at increased stroke risk. Unfortunately, a significant proportion of patients do not receive adequate anticoagulant therapy due to increased or prohibitive hemorrhagic risk. The observation that most thrombi are generated in the left atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The therapeutic attitude shown in our study is similar to that reported in non-CKD patients [22], however the excess of early bleeding should lead us to reconsider whether it is really necessary, in patients with such a high risk of bleeding, to take two drugs rather than one after the procedure.In fact, there are many doubts about the use of dual antiplatelet agents in dialysis patient even in the presence of other clinical situations, such as ischemic heart disease [23]. Recently, even among cardiologists, the need to always prescribe double antiplatelet therapy after LAA occlusion has been questioned, and several registry data suggest that single antiplatelet therapy is just as effective as double antiplatelet therapy [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic attitude shown in our study is similar to that reported in non-CKD patients [22], however the excess of early bleeding should lead us to reconsider whether it is really necessary, in patients with such a high risk of bleeding, to take two drugs rather than one after the procedure.In fact, there are many doubts about the use of dual antiplatelet agents in dialysis patient even in the presence of other clinical situations, such as ischemic heart disease [23]. Recently, even among cardiologists, the need to always prescribe double antiplatelet therapy after LAA occlusion has been questioned, and several registry data suggest that single antiplatelet therapy is just as effective as double antiplatelet therapy [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous left-atrial appendage occlusion (LAAO) is an alternative for patients with AF who have a contraindication for long-term OAT [3,[69][70][71][72][73].…”
Section: Left-atrial Appendage Percutaneous Occlusionmentioning
confidence: 99%
“…LAAO has been shown to be a valid option with AF patients with high thromboembolic risk and OAT contraindication [74]. Patients with clinically manifesting CAA and AF represent ideal candidates for LAAO, as they frequently have an absolute contraindication to anticoagulant therapies [70,75].…”
Section: Left-atrial Appendage Percutaneous Occlusionmentioning
confidence: 99%
“…The aging of global populations is increasing the incidence of non-valvular atrial fibrillation (NVAF), the most common form of cardiac arrhythmia among adults [ 1 , 2 ], particularly among the elderly [ 3 ]. Extensive research has demonstrated that when used to treat patients with NVAF, anticoagulation therapy can reduce the risk of ischemic cerebral vascularization by 60% and mortality by 30% [ 4 ]. However, compliance with treatment regimens is a serious issue, particularly when dealing with conditions that require long-term therapy, such as NVAF [ 5 ].…”
Section: Introductionmentioning
confidence: 99%